2021
DOI: 10.2215/cjn.01910221
|View full text |Cite
|
Sign up to set email alerts
|

Kidney Disease among People Who Are Incarcerated

Abstract: Chronic kidney disease (CKD) affects 15% of US adults and is associated with increased morbidity and mortality. CKD disproportionately impacts certain populations, including racial and ethnic minorities and individuals from disadvantaged socioeconomic backgrounds. These groups are also disproportionately impacted by incarceration and barriers to accessing health services. Incarceration represents an opportunity to link marginalized individuals to CKD care. Despite a legal obligation to provide a community stan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 55 publications
(68 reference statements)
0
2
0
Order By: Relevance
“…La DP es una terapia 100% domiciliaria, que brinda la oportunidad a los pacientes de ser responsables de su propia salud y bienestar, pudiéndose realizar de forma eficaz en una población carcelaria. Se han reportado casos de reclusos, que han realizado de manera óptima su diálisis durante el tiempo que estuvieron en prisión 11 .…”
Section: Discussionunclassified
See 1 more Smart Citation
“…La DP es una terapia 100% domiciliaria, que brinda la oportunidad a los pacientes de ser responsables de su propia salud y bienestar, pudiéndose realizar de forma eficaz en una población carcelaria. Se han reportado casos de reclusos, que han realizado de manera óptima su diálisis durante el tiempo que estuvieron en prisión 11 .…”
Section: Discussionunclassified
“…Se inició así el proyecto «Hemodiálisis domiciliaria en la cárcel», realizando sesiones de HD a presos de alta vigilancia con un solo policía; sin eventos adversos graves, habiendo además disminución en el tiempo y costo del transporte. Por otro lado, en Connecticut se reportó un estudio piloto que describe casos de pacientes reclusos, con buenos resultados clínicos, sin muchas complicaciones 11 . En nuestro reporte de caso se evidencia que el paciente durante su estancia en el centro penitenciario no presentó complicaciones infecciosas ni mecánicas asociadas a la DP, además de que no hubo necesidad de hospitalización; la transfusión sanguínea se coordinó para ser realizada en prisión.…”
Section: Discussionunclassified
“…The clinical biochemical indicators that were statistically different among the three groups (12) were correlated with the brain morphological indicators that were statistically different among the three groups (58). The methods of correlation analysis were as follows: (1) two measures that conformed to a normal distribution were analyzed using Pearson's correlation; (2) two measures, at least one of which did not conform to a normal distribution, were analyzed using Spearman's correlation; and (3) categorical variables associated with numerical variables were analyzed using the Eta-squared coe cient.…”
Section: Statistical Analysis Of Datamentioning
confidence: 99%
“…The latter two were more sensitive to brain alterations in patients with CKD; an analysis of the results revealed that the reduction in cortical thickness was predominantly concentrated in the fusiform gyrus, inferior temporal gyrus, lateral occipital cortex, and lingual gyrus. In hippocampus is capable of recalling events that have transpired(Miglinas et al, 2020;Murphy et al, 2021). The temporal lobe is also involved in mental management, and once structural changes occur in the temporal lobe, patients will experience mental and behavioral abnormalities(Narasimhan et al, 2022).…”
mentioning
confidence: 99%
“…The global mortality rate of CKD has increased by over 40% since the 1990s [ 1 , 4 ]. Nationwide, kidney disease creates millions of dollars in healthcare costs, and the economic burden continues to rise [ 5 ]. Social determinants of health (SDOH) may contribute to disparities in CKD.…”
Section: Introductionmentioning
confidence: 99%